MANAGEMENT AND UTILIZATION OF TURTLE CONSERVATION AREAS, SOCIO-ECOLOGICAL SYSTEMS, ECOSYSTEM SERVICES. - Asfahani Sauky, M.
This research is motivated by the importance of SDGs (Sustainable Development Goals) 14 in the sustainable development of marine ecosystems. Maintaining the sustainability of coastal sea areas so that they are free from any threats caused by natural or human factors is one of the efforts to realize the succession of SDGS 14. However, currently there are still many problems in marine coastal development, one of which is the issue of sustainability of sea turtle species. Commercial and consumptive exploitation of turtle species is often carried out, resulting in disruption of the sustainability of turtle species and their ecosystems.